Coefficient Estimates for Certain Subclasses of Bi-Univalent Functions - Nurdiana Nurali; Aini Janteng; Rashidah Omar (HIKARI Ltd, 2018)
Let Σ denote the class of bi-univalent functions in D = {z ∈ C : |z| < 1}. In this paper, we consider two subclasses of Σ defined in the open unit disk D which are denoted by S ∗ s,Σ (φ) and Cs,Σ(φ). Besides, we find upper bounds for the second and third coefficients for functions in these subclasses.